Leaving Breezy Street : a memoir - Myers-Powell, Brenda; Reynolds, April (Henry Holt and Company, 2021)
"Leaving Breezy Street is the account of a woman who had to make the best out of tough situations and limited options. A testimony on how the cycle of abuse can be perpetuated-but also broken. Proof of the transformation power of love between biological and chosen family. This is the raw truth of what American life can be like for so many people"--